The common motives for appendectomy in Hail Region Saudi Arabia - Fawaz D Alshammari; Hanan A Oreiby; Hussain Gadelkarim Ahmed; Khalid Alshaghdali; Jerold C Alcantara; Gamal Mohamed Elawad Ahmed; Sara A Seifeldin; Emad Abboh Abdallah Abboh; Waleed Mansi Al Shammari; Fawzia Mutasim M Al Tayeeb; Bandar S Al Saif; Ali Ahmed Al Qahtani; et al. (AIMS Press, 2020)
Background: Appendectomy remains the most common emergency surgery. With the lack of literature from Saudi Arabia regarding the treatment for appendix disorders, this study aimed to identify the common motives for appendectomy in Northern Saudi Arabia. Methodology: Data referring to be resected appendix patients who were diagnosed during the period from January 2018 to December 2018 were included in the present study. The diagnosis of the resected appendix was confirmed by conventional histopathology. Results: The most common cause for the appendectomy was acute appendicitis followed by gangrenous perforated appendicitis, chronic appendicitis, and lymphoid hyperplasia, representing 85/129(66%), 33/129(26%), 8/129(6%), and 3/129(2%), in this order. Conclusion: Appendectomy is a common procedure for the treatment of a large section of patients with appendicitis and appendicitis like clinical features. Acute appendicitis was the most motive for appendectomy followed by gangrenous perforated appendicitis in Northern Saudi Arabia.